Biaxial tensile drawing of poly(ethylene terephthalate) via environmental crazing as a method for creating a porous structure. (5th December 2018) - Yarysheva, A. Yu; Arzhakova, O.V.; Yarysheva, L.M.; Volynskii, A.L.
Abstract: Crazing of poly(ethylene terephthalate) thin film has been studied upon its successive biaxial drawing in adsorption-active liquid media in two mutually perpendicular directions. During both primary and secondary drawing, crazes propagate in the direction perpendicular to the drawing axes, thereby leading to the formation of crazes oriented orthogonally relative to each other in the polymer. The secondary drawing occurs at values of elastic modulus, stress, and tensile strain that corresponds to the onset of orientation-induced strengthening decreased due to a lower fraction of undeformed polymer available for crazing. It has been shown that, as compared with the uniaxial drawing, the biaxial deformation of polymers via the crazing mechanism leads to a higher porosity. After the removal of a liquid medium, deformed polymers partly retain their open porosity and remain to be permeable to water vapor, with the vapor permeability being higher for biaxially deformed polymers. Thus, the biaxial crazing is a promising method for the creation of breathful and porous membrane materials, as well as nanocomposites based on them. Graphical abstract: Highlights: Сrazing allows preparation of porous materials. Primary crazes control the mechanical characteristics of polymers. Secondary crazes are nucleated on primary crazes. Craze growth proceeds in the direction perpendicular to the drawing axis.